2020
DOI: 10.1021/acs.langmuir.0c00808
|View full text |Cite
|
Sign up to set email alerts
|

Surprising Lack of Influence on Water Droplet Motion by Hydrophilic Microdomains on Checkerboard-like Surfaces with Matched Contact Angle Hysteresis

Abstract: Chemically and spatially micropatterned surfaces have been successfully prepared for a number of diverse applications, including water/fog harvesting, screen printing, microfluidics, and cell/protein assays. While there have been quite some reports on micropatterned surfaces, less is known about the factors that influence dynamic surface wettability. To that end, smooth checkerboard-like micropatterned hydrophobic/(super)hydrophilic surfaces (2, 5, 10, 20 μm pattern sizes) with regions of matching/mismatching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
2
9
1
Order By: Relevance
“…In each measurement recorded after the same time, the contact angle of the sample produced using upsized VFD processing was higher than that of the sample produced using conventional autoclave processing. Surface roughness has an impact on the contact angle; the smoother the surface, the lesser the wettability, resulting in a more hydrophobic surface and therefore a higher contact angle . In the context of the present study, Becher-Nienhaus et al reported that with a reduction in surface roughness from 2.5 to 0.5 nm, the water contact angle for nanoparticles of TiO 2 increased from 45 to 58° and also found that with a reduction in particle size-squared value from 300 to 250 μm 2 , the water contact angle of starch granules’ surfaces increased from 38 to 65°.…”
Section: Results and Discussionsupporting
confidence: 48%
“…In each measurement recorded after the same time, the contact angle of the sample produced using upsized VFD processing was higher than that of the sample produced using conventional autoclave processing. Surface roughness has an impact on the contact angle; the smoother the surface, the lesser the wettability, resulting in a more hydrophobic surface and therefore a higher contact angle . In the context of the present study, Becher-Nienhaus et al reported that with a reduction in surface roughness from 2.5 to 0.5 nm, the water contact angle for nanoparticles of TiO 2 increased from 45 to 58° and also found that with a reduction in particle size-squared value from 300 to 250 μm 2 , the water contact angle of starch granules’ surfaces increased from 38 to 65°.…”
Section: Results and Discussionsupporting
confidence: 48%
“…Advancing and receding contact angle data for water droplets on checkerboard-like composite surfaces (data from Becher-Nienhaus et al …”
Section: Discussion Of Literature Datamentioning
confidence: 99%
“…When eq was first published in 1948 it was not clear whether it would be the most appropriate theory to describe droplet states on smooth composite surfaces. However, the work in 1992 by Laibinis and Whitesides on the wettability of composite surfaces created from mixed self-assembled monolayers adsorbed from solution onto surfaces of copper, silver, and gold films appeared to settle any debate. , Recently, work by Becher-Nienhaus et al on smooth checkerboard-like micropatterned hydrophobic/hydrophilic/complete wetting surfaces with regions of matching/mismatching contact angle hysteresis (CAH) has questioned whether eq accurately describes experimental data . Their surfaces used four types of surface chemistry, encompassing hydrophobic (with low and high CAH), hydrophilic (with low CAH), and complete wetting properties for water droplets.…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that different T values were related to different SAs. When the T was small, the length of the adjacent pinning points was shorter, the number of pinning segments of liquid droplets on the solid surface increased, the three-phase contact line was more continuous and prone to deformation, and the movement of the three-phase contact line was difficult and the droplet was difficult to slide. The SA of the random pit samples was affected by the continuity of the three-phase contact line. For the same SA of random pits, the T value shows dispersion.…”
Section: Methodsmentioning
confidence: 99%